2018
DOI: 10.1080/10428194.2018.1443449
|View full text |Cite
|
Sign up to set email alerts
|

Pilot trial of K562/GM-CSF whole-cell vaccination in MDS patients

Abstract: Myelodysplastic syndromes (MDS) are a heterogeneous group of clonal hematopoietic stem cell malignancies. Currently, approved drugs are given with non-curative intent as the only known cure is allogeneic bone marrow transplantation, which relies on the donor's immune system driving an allogeneic effect. Previous efforts to harness the endogenous immune system have been less successful. We present the results of a pilot study of K562/GM-CSF (GVAX) whole-cell vaccination in MDS patients. The primary objective of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…We further showed the same regimen was effective in rhesus macaques as it was capable of inducing authentic neutralizing antibody to a level 3-fold higher than human convalescent sera, suggesting the possibility of successful translation to human clinical trials. K562-derived whole-cell vaccine approach has been previously explored for cancer treatment by engineering K562 to express immune-regulatory cytokines, and more recently tumor antigen [17][18][19]. Such exploration established the safety of inactivated K562-derived vaccine for human use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We further showed the same regimen was effective in rhesus macaques as it was capable of inducing authentic neutralizing antibody to a level 3-fold higher than human convalescent sera, suggesting the possibility of successful translation to human clinical trials. K562-derived whole-cell vaccine approach has been previously explored for cancer treatment by engineering K562 to express immune-regulatory cytokines, and more recently tumor antigen [17][18][19]. Such exploration established the safety of inactivated K562-derived vaccine for human use.…”
Section: Discussionmentioning
confidence: 99%
“…K562-derived whole-cell vaccine approach has been previously explored for cancer treatment by engineering K562 to express immune-regulatory cytokines, and more recently tumour antigen [ 17–19 ]. Such exploration established the safety of inactivated K562-derived vaccine for human use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A randomized study comparing K562 GVAX versus interferon plus GM‐CSF for patients failing to achieve molecular remission after tyrosine kinase therapy in CML has been initiated (NCT00363649). A smaller trial of K562 GVAX in MDS demonstrated safety and feasibility but no clear clinical responses 79 . In myeloma patients receiving lenalidomide, vaccination with allogeneic myeloma lines, K562/GM, and Prevnar‐13 converted eight of 15 myeloma patients from a near CR to a full CR with tumor‐specific immunity demonstrated 80 …”
Section: Gvax In Hematologic Malignancies and Hematopoietic Cell Transplantationmentioning
confidence: 99%
“…We determined the prophylactic and therapeutic effects of the IFNs produced by the antiviral T-cell Biofactory platform on SARS-CoV-2 infected cells and investigated the expression profiles of ISGs in the host cells in response to these IFNs. We also determined the radiation dose (γ-radiation) needed to render the T-cell Biofactory non-proliferative making the cellular products suitable for clinical use 17,[20][21][22] , while conserving the cell-based IFN production. This process ensures safe administration of the T-cell Biofactory without potential oncogenesis.…”
Section: Introductionmentioning
confidence: 99%